Moral and legal education of high school students - MAKAROV, Alexey (Journal of Education, Technology and Computer Science, 2014)
The article discusses the nature and significance of moral and legal educationof high school students as a basic psychological and educational problem.The author analyses scientific positions of educational classics and makes anattempt to distinguish benchmarks helping to improve the moral and legal cultureof high school students.